Cytokine/Chemokine Responses in Activated CD4(+) and CD8(+) T Cells Isolated from Peripheral Blood, Bone Marrow, and Axillary Lymph Nodes during Acute Simian Immunodeficiency Virus Infection - Kenway-Lynch, Carys S. (American Society for Microbiology, 2014)
Understanding the cytokine/chemokine networks in CD4(+) and CD8(+) T cells during the acute phase of infection is crucial to design therapies for the control of early human immunodeficiency virus (HIV)/simian immunodeficiency virus (SIV) replication. Here, we measured early changes in CD4(+) and CD8(+) T cells in the peripheral blood (PB), bone marrow (BM), and axillary lymph node (ALN) tissue of rhesus macaques infected with SIV(MAC)251. At 21 days after infection, all tissues showed a statistically significant loss of CD4(+) T cells along with immune activation of CD8(+) T cells in PB and ALN tissue. Twenty-eight different cytokines/chemokines were quantified in either anti-CD3/28 antibody- or staphylococcal enterotoxin B-stimulated single-positive CD4(+) and CD8(+) T cells. PB CD4(+) T cells produced predominantly interleukin-2 (IL-2), whereas CD4(+) and CD8(+) T-cell subsets in tissues produced β-chemokines both before and 21 days after SIV infection. Tissues generally exhibited massive upregulation of many cytokines/chemokines following infection, possibly in an attempt to mitigate the loss of CD4(+) T cells. There was no evidence of a T-helper 1 (T(H)1)-to-T(H)2 shift in CD4(+) T cells or a T-cytotoxic 1 (T(C)1)-to-T(C)2 cytokine shift in CD8(+) T cells in PB, BM, and ALN T-cell subsets during the acute phase of SIV infection. Despite the upregulation of several important effector cytokines/chemokines (IL-2, IL-12, IL-17, gamma interferon, granulocyte-macrophage colony-stimulating factor) by CD4(+) and CD8(+) T cells, upregulation of β-chemokines (CCL2 and CCL22), basic fibroblast growth factor (FGF-basic), hepatocyte growth factor (HGF), and migration inhibition factor (MIF) may provide a poor prognosis either by inducing increased virus replication or by other unknown mechanisms. Therefore, drugs targeting β-chemokines (CCL2 and CCL22), FGF-basic, HGF, or MIF might be important for developing effective vaccines and therapeutics against HIV. IMPORTANCE Human immunodeficiency virus (HIV)/simian immunodeficiency virus (SIV) infection results in early depletion of CD4(+) T cells and dysregulation of protective immune responses. Therefore, understanding the cytokine/chemokine networks in CD4(+) and CD8(+) T cells in different tissues during the acute phase of infection is crucial to the design of therapies for the control of early viral replication. Here, we measured early changes in CD4(+) and CD8(+) T cells in peripheral blood (PB), bone marrow (BM), and axillary lymph node (ALN) tissue of rhesus macaques infected with SIV(MAC)251. There was no evidence of a T-helper 1 (T(H)1)-to-T(H)2 shift in CD4(+) T cells or a T-cytotoxic 1 (T(C)1)-to-T(C)2 cytokine shift in CD8(+) T cells in PB, BM, and ALN T-cell subsets during the acute phase of SIV infection. Despite the upregulation of several important effector cytokines/chemokines by CD4(+) and CD8(+) T cells, upregulation of β-chemokines, fibroblast growth factor-basic, hepatocyte growth factor, and migration inhibition factor may provide a poor prognosis.